ANALISIS EKONOMI DAN TINGKAT KESEJAHTRAAN RUMAHTANGGA PETANI PESERTA PROGRAM HUTAN KEMASYARAKATAN (HKM) DI KECAMATAN SAMBALIA, KABUPATEN LOMBOK TIMUR NTB - M. YUSUF; DUDI SEPTIADI; MUHAMMAD NURSAN; FADLI FADLI (Universitas Mahasaraswati K. Mataram, 2023)
The aims of this research are to: (1) analyze the income of farmers from the Community Forestry (Hkm) program in Sambelia District, East Lombok Regency; (2) Analyze the contribution of farmers' income from the Community Forestry (HKm) program to HKm Farmer household income in Sambelia District, East Lombok Regency and (3) Analyze the level of welfare of farmer households from the Community Forestry program in Sambelia District, East Lombok Regency. The method used is descriptive method, while data collection is done by survey technique. Data were analyzed descriptively. The results showed that: (1) The average household income of HKm farmers participating in the HKm program in Samblia district, East Lombok Regency was IDR 21,657,140/year or IDR 1,804,762/year. month; (2) The HKm program household income contribution is 71.09%, while non-HKm (outside HKm) is 28.91%; and (3) the level of well-being of participating HKm farmer households based on the category of well-being level and/or poverty level according to the World Bank, BPS criteria, Sayogyo found that all three well-being standards give results slightly different. Under the BPS criteria, the farmer household participating in the HKm program in Sambalia district, East Lombok, is classified as non-poor. Although in general the categories were like this, after a deeper study, 30.30 percent of the respondents were in the poor category and 69.70 percent in the non-poor category. Based on World Bank criteria, HKm farmer households were found not to be in the poor category, but in fact there were 24.24% of respondents who were in the poor category and 73.70% were not. They were poor. Meanwhile, according to the Sayogyo criteria, HKm participating farmer households were in the category of 60.61% non-poor, 27.27% near poor, 12.12% poor and not very poor.